Improving Students Pronounciation Skills by Using Songs at 11th Grade of SMK Pangeran Jayakarta - Fitria, Rahmadhani; Asrori, Ircham (Jurnal Web Informatika Teknologi, 2022)
The purpose of this study was to determine whether using media such as English songs could improve the pronounciation skills of 11th grade students at SMK Pangeran Jayakarta. When the researcher conducts the PPL, the researcher notices that the students’ ability to pronounce the words remains low, and they find it difficult to pronounce the words given by the researcher. It makes the student nervous and uninterested in pronouncing or speaking English. English songs can be used by English teachers at all levels to teach pronounciation. This study employs classroom action research. It was divides into two cycles. The findings revealed that students’ test scores have improved. The outcome was derived from students’ pronounciation scores. It demonstrated that teaching pronouciation through the use of English song is effective in the teaching-learning process.